DISPLASIA KRANIOFASIAL AKIBAT GANGGUAN TUMBUH KEMBANG MENURUT PATOMORFOGENESIS - Miesje Karmiati Purwanegara (Faculty of Dentistry, Universitas Indonesia, 2015)
Craniofacial dysplasias are rarely found, but the frequency of cleft lip and palate in Indonesia is quite high. Accurate observation and identification this dysplasia should be done before treatment. To recognize the craniofacial dysplasia need a classification. One of the classifications is based on pathomorphogenic. This classification will identify the craniofacial dysplasia from stage of development, oritigin, form and site. The clinicians will manage those patients accurately with this classification and the patient's quality of life will be improved.